Metode CTL (Contextual Teaching And Learning ) Berbantu Media Audio Visual dalam Meningkatkan Hasil Belajar Siswa SD N 200311 - Ritonga, Robiah Hasna (Darul Ilmi: Jurnal Ilmu Kependidikan dan Keislaman, 2022)
Islamic Religious Education learning is dominated by teachers and inadequate learning media makes students only get information from the teacher so that the learning process becomes monotonous and teacher-centered. Situations like this can lead to boredom of students towards learning, students become less active and cause student learning outcomes to be low. Seeing this fact, the researcher offers a CTL (Contextual Teaching And Learning) learning method assisted by audio-visual media. Based on this, the researcher aims to determine the improvement of student learning outcomes in learning Islamic Religious Education through the CTL method assisted by audio-visual media in class V SD N 200311 Padangsidimpuan. The type of this research methodology is classroom action research (CAR) which is descriptive qualitative in nature, which describes the results of research according to those obtained in the field. Based on the results of research on students with the Application of the Audio Visual Assisted CTL Method, it was found that the data showed an increase in student learning outcomes. Student learning outcomes have increased in cycle I and cycle II through the application of the CTL method assisted by audio-visual media in class V SD N 200311 Padangsidmpuan. It can be concluded that there is an increase in student learning outcomes in Islamic Religious Education subjects through CTL assisted by audio-visual media at V SD N 200311 Padangsidimpuan.